Urinary Trans, Trans-Muconic Acid is Not a Reliable Biomarker for Low-level Environmental and Occupational Benzene Exposures - Amir Jalai; Zahra Ramezani; Karim Ebrahim (Safety and Health at Work, 2017)
Background: Benzene is a known occupational and environmental pollutant. Its urinary metabolite trans, trans-muconic acid (tt-MA) has been introduced by some environmental and occupational health regulatory associations as a biological index for the assessment of benzene exposure; however, recently, doubts have been raised about the specificity of tt-MA for low-level benzene exposures. In the present study, we investigated the association between urinary levels of tt-MA and inhalational exposure to benzene in different exposure groups. Methods: Benzene exposure was assessed by personal air sampling. Collected benzene on charcoal tube was extracted by carbon disulfide and determined by a gas chromatograph (gas chromatography with a flame ionization detector). Urinary tt-MA was extracted by a strong anion-exchange column and determined with high-performance liquid chromatography–UV. Results: Urinary levels of tt-MA in intensive benzene exposure groups (chemical workers and police officers) were significantly higher than other groups (urban and rural residents), but its levels in the last two groups with significant different exposure levels (mean = 0.081 ppm and 0.019 ppm, respectively) showed no significant difference (mean = 388 μg/g creatinine and 282 μg/g, respectively; p < 0.05). Before work shift, urine samples of workers and police officers showed a high amount of tt-MA and its levels in rural residents’ samples were not zero. Conclusion: Our results suggest that tt-MA may not be a reliable biomarker for monitoring low-level (below 0.5 ppm) benzene exposures.